Efek Temperatur Pengarangan Cangkang Kerang dan Tulang Sapi Terhadap Proximate - Mohammad Nurhilal; Rosita Dwityaningsih; Theresia Evila Purwanti Sri Rahayu; Radhi Ariawan (P3M Politeknik Negeri Cilacap, 2022)
Studies on the use of animal waste as charcoal ingredient in the needs of activated charcoal material has been carried out and developed. Activated charcoal is produced through activation process at a certain temperature, condition, and time in order to creat a higher carbon content in charcoal . One of the important factors in the manufacture of activated charcoal is the temperature during the production process. The purpose of this study is to discuss the influence of temperature factor of mussel shells and beef bones on water content, ash content, volatile matter and fixed carbon during the charcoal production process. The research is carried out through experimental method of making chorcoal with temperature variations of 400, 500, 600, 700, and 800 oC. The result of the experiment shows the highest ash content and water content found respectively in beef bone charcoal of 800 oC which is 98,697 %, and of 400 oC which is 4,942 %, while the highest volatile matter and fixed carbon levels are found in clam shell charcoal of 800 oC which is 6,717 %, and of 500 oC which is 43,282 %. The result concluded that the effect of the temperature of the production process affects the water content, ash, volatile matter and fixed carbon.